Habermas : introduction and analysis - Ingram, David, 1952- (Cornell University Press, 2010)
"This is a marvelous resource for anyone interested in better understanding the difficult and voluminous work of jurgen Habermas. It is clearly written, comprehensive, and fair-minded in its exegesis; moreover, it provides at the same time a highly intelligent, critical analysis of central themes in the writings of Habermas."--Stephen K. White, James Hart Professor of Politics, University of Virginia.
Keywords: Habermas, Jürgen.; Habermas, Jürgen; Social sciences -- Philosophy.; Sciences sociales -- Philosophie.; PHILOSOPHY -- History & Surveys -- Modern.; Social sciences -- Philosophy